1999
DOI: 10.1128/jcm.37.5.1567-1569.1999
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation of the Automated Cobas Amplicor HCV Assay Improves Sensitivity of Hepatitis C Virus RNA Detection and Yields Results That Are More Clinically Relevant

Abstract: The first and second generations of the Cobas Amplicor HCV assay were compared among patients at risk of hepatitis C virus (HCV) infection. The second-generation test was found to be of greater sensitivity and of good specificity among clinical specimens containing HCV RNA of different genotypes. Finally, this new test is shown to predict the outcome of interferon therapy better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 10 publications
(10 reference statements)
1
31
0
Order By: Relevance
“…Serum HCV RNA was assessed by qualitative PCR assay (COBAS Amplicor HCV Monitor Test v2.0, Chugai-Roche Diagnostics), with a detection limit of 50 IU/mL [12].…”
Section: Virological Testsmentioning
confidence: 99%
“…Serum HCV RNA was assessed by qualitative PCR assay (COBAS Amplicor HCV Monitor Test v2.0, Chugai-Roche Diagnostics), with a detection limit of 50 IU/mL [12].…”
Section: Virological Testsmentioning
confidence: 99%
“…Structural proteins Non-structural proteins studies between a standardized RT±PCR assay for the detection and quanti®cation of HCV RNA (AMPLICOR HCV MONITOR ä ) and the bDNA assay (Quantiplex ä HCV assay) have shown that the AMPLICOR HCV Test is more sensitive and, in some rare cases, more predictive of long-term response to IFN therapy, than bDNA [20]. A second-generation AMPLICOR HCV assay, which has greater sensitivity, has been introduced [27]. The problem remains, however, that as each assay uses different standard values, the assays cannot be directly compared with each other.…”
Section: Hcv Diagnosticsmentioning
confidence: 99%
“…As shown in the present study, 204 (95.8%) of 213 cases were detectable by the second-generation assay, providing evidence that sensitivity was indeed significantly improved. The sensitivity of this assay was comparable with that of the COBAS v2.0 assay, a well-calibrated, sensitive and non-serotype-dependent assay (8,(17)(18)(19)(20)(24)(25)(26).…”
Section: Figmentioning
confidence: 73%
“…The quantification of HCV has become an important issue because low viral load is a strong predictor of sustained response to interferon (IFN) monotherapy for chronic hepatitis C (13-15). Among the assays for quantification of HCV load, combined reverse transcription PCR assay, the AM-PLICOR HCV MONITOR assay version 2.0 (CO-BAS v2.0) (Roche Molecular Systems, Branchburg, NJ), is now one of the most sensitive and reliable assays (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%